Manajemen Pembiayaan Pendidikan untuk Meningkatkan Mutu Pendidikan - Amanati, Putri; Mukhlisa, Adinda Siti; Suharyat, Yayat (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to analyze education financing management based on the effectiveness and efficiency of education financing management and the use of technology in education financing management. This research uses descriptive qualitative research methods with secondary data collected through literature studies and analyzed qualitatively by reducing displays and concluding results. The results of this study indicate that effective and efficient education financing management in educational institutions is key to supporting the achievement of quality education goals. The management of education financial resources must pay attention to the essential stages, because education financing is considered an investment in human resource development. In this context, the effectiveness and efficiency of education cost management is essential to maximize educational outcomes. The current development of digital technology opens up great opportunities to optimally utilize the education financing system. With the adoption of information and communication technology, educational institutions can automate the financing process, integrate digital payment systems, and enable real-time monitoring of fund flows and financial reporting.